The Role of Citizenship Education in Countering Political Disinformation in the Era of Society 5.0 - Taufiqurrahman, Muhammad; Purborini, Vivi Sylvia (Ilomata International Journal of Social Science, 2025)
Technological developments in the Society 5.0 era have brought easier access to information, but also pose serious challenges in the form of rampant political disinformation that can undermine democratic stability. This study aims to analyze the role of Civics Education (PKn) in countering political disinformation by strengthening digital literacy, political literacy, and national character values. The research method used was a descriptive qualitative approach, through a review of scientific literature from various credible sources relevant to the topic. The results indicate that PKn plays a strategic role as a critical educational instrument that equips students with the skills to filter information, think reflectively, and internalize civic dispositions such as honesty, responsibility, and tolerance. Furthermore, the integration of digital technology into PKn learning through case-based strategies, problem-based learning, and online discussion forums has proven effective in increasing student participation and building democratic awareness. In conclusion, adaptive transformation of PKn to the demands of the Society 5.0 era is key to shaping a digital generation that is intelligent, wise, and has character, while simultaneously strengthening the resilience of Indonesian democracy. In facing political disinformation, citizenship education is no longer an option it is an urgent necessity. This education must evolve to equip citizens with strong cognitive defenses, critical digital literacy, responsible digital ethics, and a commitment to social cohesion. By investing in this transformative education, we can empower individuals to become resilient and informed citizens who are able to navigate the complex information landscape and contribute to the health of democracy in the digital age.